Efficacy of the Chinese herbal medicine Jintiange capsules in the postoperative treatment of osteoporotic vertebral compression fractures: a systematic review and meta-analysis - Fu, Yongsheng; Wang, Weiguo; Zhao, Minghua; Zhao, Jianpeng; Tan, Mingyue (Frontiers in Medicine, 2023)
Background In traditional Chinese medicine, Jintiange capsules are frequently used to treat metabolic bone diseases and strengthen bones and tendons. The main component of Jintiange capsules is bionic tiger bone powder. However, the active ingredients and proteins are derived from other animal bones, with chemical profiles similar to that of natural tiger bone. This study aimed to explore the efficacy of Jintiange capsules, a Chinese herbal medicine, in the postoperative treatment of osteoporotic vertebral compression fractures (OVCFs). Methods In this systematic review, literature was retrieved using PubMed, the Cochrane Library, the Chinese National Knowledge Infrastructure, the Web of Science, the Wanfang Database, the Chinese Biomedical Literature Database, and the Chinese VIP Database from inception to July 2023. The primary outcome measures were the bone mineral density (BMD) and effective rate. The secondary outcome measures were the visual analog pain score (VAS), Oswestry disability index (ODI), Cobb’s angle, serum osteocalcin, serum alkaline phosphatase, and adverse events. RevMan 5.4 and STATA 17.0 software were used for data analysis. Results We enrolled randomized controlled trials (RCTs) focusing on 1,642 patients in the meta-analysis. The meta-analysis illustrated that Jintiange capsules significantly increased the BMD of the lumbar spine (p < 0.00001), femoral neck (p = 0.0005), and whole body (p = 0.01). The subgroup analysis of Jintiange capsules combination therapy showed that the BMD of the lumbar spine and whole body was significantly improved with Jintiange capsules (p < 0.00001). The test for the overall effect showed that Jintiange capsules had a significantly higher effective rate than the control groups (p = 0.003). Additionally, the overall effect test showed that Jintiange capsules decreased the VAS and ODI (p < 0.00001) and Cobb’s angle (p = 0.02), and improved serum OC and ALP (p < 0.00001) compared with the controls. Furthermore, the pooled analysis of adverse reactions showed no serious impacts on the treatment of OVCFs. Conclusion Jintiange capsules demonstrate high safety and efficacy in the treatment of OVCFs, including increasing BMD, the lift effect rate, serum OC levels, and pain relief, decreasing the ODI, serum ALP levels, and adverse events, and improving Cobb’s angle. Additional research is required to validate the efficacy of Jintiange capsules for the postoperative treatment of OVCFs. Systematic review registration: https://www.crd.york.ac.uk/PROSPERO.